Correlation Between Oxidative Stress Generation, Reticular Fiber Density and Testicular Histomorphometric Parameters Of Streptozotocin-Induced Diabetic Wistar Rat - Anyanwu, GE; Agbor, CA (Journal of Bio-Science, 2021)
The actual underlying mechanism of alterations in testicular histomorphometric parameters resulting from diabetes-induced oxidative stress is still not well understood because of the absence of supporting evidence from scientific experiments. This study was conducted to investigate the correlation between serum oxidative stress markers with testicular histomorphometric parameters and reticular fiber density of Streptozotocin-induced diabetic Wistar rat. The experiment included twenty eight adult male rats sorted into four groups, Group A (Control), other animals were sorted into treatment groups based on their blood glucose levels after inducing diabetes with 65 mg/kg/bw of streptozotocin, Groups B (100 - 200 mmol/l), Group C (210 - 250 mmol/l), Group D (260 - 300 mmol/l). At termination, Serum superoxide dimutase (SOD), catalase and melondialdehyde where evaluated using reagent based antioxidant enzyme assay while reticulum stain kits was used to demonstrate for reticular fiber density. Histomorphometric measurements were carried out using ocular micrometer after calibration on a light microscope. Statistical analysis was done using analysis of variance with p<0.05 considered significant. Results reveal that the higher the blood glucose levels in diabetic animals, the higher the serum concentration of oxidative stress markers. Density of reticular fiber increased with increase in blood glucose levels, while tubular diameter and epithelial height decreased with increase in increase in hyperglycaemic levels. In conclusion, there was a progressive increase in reticular fiber density and decrease in tubular diameter and epithelial height as a consequence of increase oxidative stress generation in diabetic model. J. Bio-Sci. 29(2): 01-08, 2021 (December)